2023
DOI: 10.21203/rs.3.rs-2508994/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Discrepancy of Unmet Needs on Contraception in Indonesia: Urban vs. Rural Area: A Cross-Sectional Study

Abstract: Indonesia Maternal Mortality Rate (MMR) 230 per 100,000 live births is considered one of the highest in Southeast Asia region. Contraception is an essential part of safe motherhood, yet most Indonesian doesn’t participate in family planning. Active use of contraception on fertile couples was 62.5%. Based on Indonesia 2017 DHS, 11% fertile women had insufficient contraception need. Unmet need for contraception might contribute to the burden of MMR. A cross-sectional study was conducted to analyse which factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Serum Patients with PCOS have serum AMH levels that are 2-3 times higher than those of healthy women. Study revealed that AMH levels may be utilized as a predictor in the diagnosis of PCOS as an alternative to analyzing polycystic ovary pictures and the incidence of PCOS increases as AMH levels rise (Harzif et al, 2023). Wiweko et al (2014) discovered that people with high AMH levels were 9 times more likely to have PCOS, with the AMH cutoff value as a predictor of PCOS being 4.45 ng/mL.…”
Section: Amh Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Serum Patients with PCOS have serum AMH levels that are 2-3 times higher than those of healthy women. Study revealed that AMH levels may be utilized as a predictor in the diagnosis of PCOS as an alternative to analyzing polycystic ovary pictures and the incidence of PCOS increases as AMH levels rise (Harzif et al, 2023). Wiweko et al (2014) discovered that people with high AMH levels were 9 times more likely to have PCOS, with the AMH cutoff value as a predictor of PCOS being 4.45 ng/mL.…”
Section: Amh Analysismentioning
confidence: 99%
“…FSH levels between 3 and 10 mIU/mL are considered normal, whereas values greater than 12 mIU/mL suggest decreased ovarian reserves. More than 25 mIU/mL is associated with ovarian failure and is seen in postmenopausal women (Harzif et al, 2023).…”
Section: Fsh Analysismentioning
confidence: 99%
See 1 more Smart Citation